2019
DOI: 10.31686/ijier.vol7.iss7.1590
|View full text |Cite
|
Sign up to set email alerts
|

Helping a Student with Learning Disabilities Memorize Multiplication Facts

Abstract: A sixth grade student's ability to memorize multiplication facts was investigated. The overall goal of the work was to improve the student's understanding and knowledge of basic multiplication facts (0-10) for the zeroes, to fives. There were 66 facts, for example 4 x 6 = 24. The student had been taught multiplication concepts in her elementary years and she did have a basic understand of the meaning of multiplication facts as shown on a pretest. She understood that 4 x 6 is a representation of four sets of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…It took several months for the subject in this study to memorize the multiplication facts for the ones to fives. The student was quite successful at reciting the multiplication facts for the ones to fives, using skip counting on her fingers [1].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It took several months for the subject in this study to memorize the multiplication facts for the ones to fives. The student was quite successful at reciting the multiplication facts for the ones to fives, using skip counting on her fingers [1].…”
Section: Discussionmentioning
confidence: 99%
“…The researcher had worked with the student in four previous studies [1], [38], [39], [40]. The student's previous knowledge and history were used to develop an individualized education plan to help her memorize multiplication facts (0-10) for the ones through fives [1]. The study showed that the student had a conceptual understanding of basic multiplication facts; but did not have them memorized.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The researcher had worked with the student in six previous studies [1], [2], [3], [4], [5], [6]. The student's previous knowledge and history were used to develop an individualized education plan to help her count money and change.…”
Section: Methodsmentioning
confidence: 99%